Местное самоуправление как социальный институт в период трансформации общества - Салморбекова, Р. (Социология: теория, методы, маркетинг, 2005)
This article is dedicated to the comparative study of local government as a social institution. We have analyzed the points of local authority forming on the different stages of civic society development as well as the major society development. The local government is considered through the prism of sociological approach in particular by means of structural-functional paradigm.